PENERAPAN MODEL PEMBELAJARAN NUMBER HEAD TOGETHER DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AL QURAN HADIST KELAS IV MIN 11 ACEH TENGGARA - Nur Aulia Putri; Suriana Suriana (UIN Sumatera Utara Medan, 2025)
This study aims to improve students' learning motivation in the subject of Al-Qur’an Hadith through the implementation of the cooperative learning model Numbered Head Together (NHT) in Grade IV at MIN 11 Aceh Tenggara. The background of this research is the low level of student motivation, which affects their lack of active participation and enthusiasm in learning. The method used is Classroom Action Research (CAR), conducted in two cycles, referring to the Arikunto model, which includes the stages of planning, implementation, observation, and reflection. Data were collected through observation, documentation, and learning motivation questionnaires. The results show an increase in students' learning motivation after the implementation of the NHT model. The average motivation score increased from 61.35 in the first cycle to 83.1 in the second cycle. These findings indicate that the NHT model is effective in enhancing student engagement, clarifying learning procedures, and creating an enjoyable and participatory learning environment. Therefore, the application of the NHT model can serve as an alternative instructional strategy to enhance students' motivation to learn, particularly in religious subjects such as Al-Qur’an Hadist.